Organic carbon burial in global lakes and reservoirs. Issue 1 (December 2017) - Mendonça, Raquel; Müller, Roger; Clow, David; Verpoorter, Charles; Raymond, Peter; Tranvik, Lars; Sobek, Sebastian
Abstract Burial in sediments removes organic carbon (OC) from the short-term biosphere-atmosphere carbon (C) cycle, and therefore prevents greenhouse gas production in natural systems. Although OC burial in lakes and reservoirs is faster than in the ocean, the magnitude of inland water OC burial is not well constrained. Here we generate the first global-scale and regionally resolved estimate of modern OC burial in lakes and reservoirs, deriving from a comprehensive compilation of literature data. We coupled statistical models to inland water area inventories to estimate a yearly OC burial of 0.15 (range, 0.06–0.25) Pg C, of which ~40% is stored in reservoirs. Relatively higher OC burial rates are predicted for warm and dry regions. While we report lower burial than previously estimated, lake and reservoir OC burial corresponded to ~20% of their C emissions, making them an important C sink that is likely to increase with eutrophication and river damming. The magnitude of organic carbon burial in lakes and reservoirs is poorly constrained. Here, using a compilation of modern data from the literature and statistical modeling, the authors estimate a global yearly organic carbon burial of 0.15 Pg C in inland waters, of which 40% is stored in reservoirs.